Hyenas/hustlers: An Afrosur/realist reading of Touki Bouki (1973). (1st December 2019) - Moji, Polo B.
AbstractUsing Amir Baraka's conception of Afrosurrealism as a black aesthetic form that is imbricated with 'lived life', this article proposes an Afrosur/realist reading of Djibril Diop Mambéty's Touki Bouki ('The hyena's journey') (1973). I explore the trajectory of the iconic lovers Anta and Mory and their recourse to petty criminality as a means of escaping to Paris. I first consider how petty criminality or 'hustling' can be read in relation to Abdoumaliq Simone's notion of 'people as infrastructure' or a realistic reproduction of the African urban. I then turn my attention to Membéty's surrealist portrayal of Anta and Mory as 'hyenas' ‐ or the archetypal figure of the stranger who poses a threat to the city's social order. Central to my analysis of the surreal as an expression of desire is the filmic reproduction of post-independence Dakar on-screen. I pay attention to place-identity, and the filmic depiction of nodes and modes of mobility as sites of potential disruption to the city as a form of social order. The article thus subverts and complicates the dichotomy between the real and the surreal as cinematic forms that reproduce the postcolonial African urban as both lived and imagined.